Osteochondroma as a Rare Cause of Lower Limb Radiculopathy: A Case Report - Seyed Habibollah Hassani; Ali Kazeminezhad; Hesam Ghadirian; Simin Mouodi (Iranian Journal of Neurosurgery)
Background and Importance: Spinal osteochondroma is a rare benign primary spinal column tumor. Its most common site is the cervical spine, and lumbar involvement is rare. Case Presentation: A 53-year-old male patient of Iranian ethnicity presented to our clinic with severe pain and acute radiculopathy in his right lower limb for 10 days. The patient did not respond to oral analgesics for pain management. When the patient was examined with magnetic resonance imaging (MRI) and computed tomography (CT) scan, a bone tumor in the inferior facet of L4 was found. The patient underwent surgery, and the tumor was completely removed. Histopathological examination revealed osteochondroma. The patient was followed up for five years after surgery; fortunately, no symptoms or signs of recurrence occurred. Conclusion: Although osteochondroma usually occurs in the cervical region, in this case, the lesion was observed in the lumbar region, with clinical features of acute radiculopathy. Therefore, osteochondroma should be considered a differential diagnosis for lower limb radiculopathies.